Coupled dark energy and dark matter from dilatation anomaly - Beyer, Joschka; Nurmi, Sami; Wetterich, Christof (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Cosmological runaway solutions may exhibit an exact dilatation symmetry in the asymptotic limit of infinite time. In this limit, the massless dilaton or cosmon could be accompanied by another massless scalar field - the bolon. At finite time, small time-dependent masses for both the cosmon and the bolon are still present due to imperfect dilatation symmetry. For a sufficiently large mass, the bolon will start oscillating and play the role of dark matter, while the cosmon is responsible for dark energy. The common origin of the mass of both fields leads to an effective interaction between dark matter and dark energy. Realistic cosmologies are possible for a simple form of the effective cosmon-bolon potential. We find an inverse bolon mass of a size where it could reduce subgalactic structure formation
Gesehen am 10.02.2014